Targeting dormancy in acute myeloid leukaemia - Doolan, Lara (2023)
Acute myeloid leukaemia (AML) represents the poorest survival rate of all leukaemias, and the majority of patients who do achieve remission relapse within 3 years. Relapse is attributed to the presence of quiescent leukaemia initiating cells (LICs) which evade standard-of-care chemotherapy that targets the proliferative bulk of the disease. Novel therapeutics which are able to target dormant LICs are therefore required to improve patient outcomes in AML. Previous work in our group generated a model for dormancy in AML using the CD34+CD38- cell line TF1a, treated with TGFβ1 and rapamycin, to enrich for dormancy. Microarray analysis and gene expression connectivity mapping were used to identify a list of FDA-approved drugs predicted to target dormancy enriched TF1a cells (TF1a-DE). In this thesis, the top 8 hits from this analysis were screened to assess their efficacy in targeting TF1a-DE cells. This identified pantoprazole, a proton pump inhibitor, as able to inhibit colony formation and chemo-sensitise TF1a-DE to AraC.